Children and the Labor Force Participation and Earnings of Parents in the Philippines - Aniceto C. Orbeta (Philippine Institute for Development Studies (PIDS), 2005)
This paper demonstrates how family size can be an important contributor to poverty in the Philippines. It examines one of the mechanisms behind this link by focusing on the relation between number of children and the decision to seek a job and parents' wage earnings. It surveys the international literature to establish how the problem has been approached and what the results are for other countries. It then formulates and tests a model using a nationally representative household survey data for the Philippines to explain what determines the decision to seek a job and the earnings of both mothers and fathers. The model specifically considered the endogeneity of the number of children in both the labor force participation and the earnings equations.
Keywords: 330; Philippines; family size; labor force participation; earnings; Kinderarbeit; Familienplanung; Armut; Arbeitsuche; Haushaltseinkommen; Philippinen